Tianma Gouteng Decoction Exerts Pregnancy-Protective Effects Against Preeclampsia via Regulation of Oxidative Stress and NO Signaling - Jin, Meiyuan; Cao, Bin; Lin, Chao; Li, Jiayong; Xu, Qiang; Ren, Qianlei; Xu, Shouying; Tang, Chao (Frontiers in Pharmacology, 2022)
Preeclampsia (PE), a pregnancy-specific syndrome with the major molecular determinants of placenta-borne oxidative stress and consequently impaired nitric oxide (NO) generation, has been considered to be one of the leading causes of maternal morbidity as well as mortality and preterm delivery worldwide. Several medical conditions have been found to be associated with increased PE risk, however, the treatment of PE remains unclear. Here, we report that Tianma Gouteng Decoction (TGD), which is used clinically for hypertension treatment, regulates oxidative stress and NO production in human extravillous trophoblast-derived TEV-1 cells. In human preeclamptic placental explants, reactive oxygen species (ROS) levels were elevated and NO production was inhibited, while TGD treatment at different periods effectively down-regulated the H2O2-induced ROS levels and significantly up-regulated the H2O2-suppressed NO production in human TEV-1 cells. Mechanistically, TGD enhanced the activity of total nitric oxide synthase (TNOS), which catalyze L-arginine oxidation into NO, and simultaneously, TGD promoted the expression of neuronal nitric oxide synthase (nNOS) and endothelial nitric oxide synthase (eNOS), two isoforms of nitric oxide synthetases (NOS) in human placenta, resulting in the increased NO generation. More importantly, TGD administration not only increased the weight gain during pregnancy and revealed a hypotensive effect, but also improved the placental weight gain and attenuated fetal growth restriction in an NG-nitro-L-arginine methyl ester (L-NAME)-induced mouse PE-like model. Our results thereby provide new insights into the role of TGD as a potentially novel treatment for PE.